Empowering users to control ads and its effects on website stickiness - Dominick Werner; Martin Adam; Alexander Benlian (Electronic Markets, 2022)
Website providers find it increasingly difficult to convince users to accept advertisements (ads) on their websites. In this study, we investigate ad quantity customization (AQC) as a practice to counter these challenges. AQC refers to the technological means through which website providers enable users to determine the amount of ads displayed on their websites. Drawing on psychological empowerment theory, we demonstrate in an online experiment with 395 participants that AQC can pay off: A website with AQC elicits significantly higher website stickiness than a website without AQC, even if the website without AQC contains no ads at all. We furthermore find that perceived empowerment, informational fit-to-task and perceived enjoyment mediate the effect of AQC on website stickiness. Our study thus contributes to Information Systems research on web customization and offers website providers actionable recommendations to keep their users involved, interested and retained.
Keywords: D91; M37; C91; 620; Empowerment; Active control; Advertisements; Stickiness